Odpowiedzi

Najlepsza Odpowiedź!
2009-12-08T19:52:29+01:00
5 3/5+(-7,4)= 5 3/5 - 7 2/5 (bo 4/10 to 2/5) = 5 3/5 - 7 2/5 = 28/5 - 37/5 = -9/5 = - 1 4/5

-12 2/3+(5 1/2)= -12 2/3 + 5 1/2 = -38/3 + 11/2 (do wspólnego) = -76/6 + 33/6 = -43/6 = -7 1/6

-4,3-(-6 1/5)= - 4 3/10 + 6 2/10 = -43/10 + 62/10 = 19/10 = 1 9/10

(1/6)-(-1/3)= 1/6 + 1/3 = 1/6 + 2/6 = 3/6 = 1/2

(-5)-(-1 3/4)= -5 + 1 3/4 = -5 + 1 3/4 = - 3 1/4

(-2,2)+(10 1/5)= - 2 1/5 + 10 1/5 = 11/5 + 51/5 = 62/5 = 12 2/5

-(-1 1/3)+(-15)= 1 1/3 - 15 = 13 2/3

-(-9)-(-4 1/4)= 9 + 4 1/4 = 13 1/4

(-3 2/5)-4,8= -3 2/5 - 4 8/10 = 3 2/5 - 4 4/5 = 17/5 - 24/5 = -7/5 = -1 2/5

2 1/3+(-5 3/5)= 2 1/3 - 5 3/5 = 7/3 - 28/5 = 35/15 - 84/15 = - 49/15 = -3 4/15
1 5 1
2009-12-08T19:54:44+01:00
5 3/5+(-7,4)= -4,4
-12 2/3+(5 1/2)= -5,5
-4,3-(-6 1/5)= -3,1
(1/6)-(-1/3)= 3/6

(-5)-(-1 3/4)= -4,25
(-2,2)+(10 1/5)= -0,2
-(-1 1/3)+(-15)= 46/3
-(-9)-(-4 1/4)= 10
(-3 2/5)-4,8= -6
2 1/3+(-5 3/5)= -2 i 1/3
2 1 2
2009-12-08T20:48:14+01:00
5 3/5+(-7,4)= 1,8
-12 2/3+(5 1/2)= -12 4/6 + 5 3/6 = 7 1/6
-4,3-(-6 1/5)= 10,5
(1/6)-(-1/3)= 1/2

(-5)-(-1 3/4)= -3,25
(-2,2)+(10 1/5)= 8
-(-1 1/3)+(-15)= 1 1/3 - 15 = 13 2/3
-(-9)-(-4 1/4)= 9 + 4,25 = 13,25
(-3 2/5)-4,8= -3,4 - 4,8 = -8,2
2 1/3+(-5 3/5)= 2 5/15 - 5 9/15 = 2 11/15